Adoptive Cellular Therapy for Pediatric Solid Tumors: Beyond Chimeric Antigen Receptor-T Cell Therapy. Issue 4 (July 2022) - Hensel, Jonathan; Metts, Jonathan; Gupta, Ajay; Ladle, Brian H.; Pilon-Thomas, Shari; Mullinax, John
Abstract: Children and adolescents with high-risk (metastatic and relapsed) solid tumors have poor outcomes despite intensive multimodal therapy, and there is a pressing need for novel therapeutic strategies. Adoptive cellular therapy (ACT) has demonstrated activity in multiple adult cancer types, and opportunity exists to expand the use of this therapy in children. Employment of immunotherapy in the pediatric population has realized only modest overall clinical trial results, with success thus far restricted mainly to antibody-based therapies and chimeric antigen receptor T-cell therapies for lymphoid malignancy. As we improve our understanding of the orchestrated cellular and molecular mechanisms involved in ACT, this will provide biologic insight and improved ACT strategies for pediatric malignancies. This review focuses on ACT strategies outside of chimeric antigen receptor T-cell therapy, including completed and ongoing clinical trials, and highlights promising preclinical data in tumor-infiltrating lymphocytes that enhance the clinical efficacy of ACT for high-risk pediatric solid tumors.